2004
DOI: 10.1128/mcb.24.19.8447-8456.2004
|View full text |Cite
|
Sign up to set email alerts
|

GRIM-19, a Cell Death Regulatory Protein, Is Essential for Assembly and Function of Mitochondrial Complex I

Abstract: Mitochondria play essential roles in cellular energy production via the oxidative phosphorylation system (OXPHOS) consisting of five multiprotein complexes and also in the initiation of apoptosis. NADH:ubiquinone oxidoreductase (complex I) is the largest complex that catalyzes the first step of electron transfer in the OXPHOS system. GRIM-19 was originally identified as a nuclear protein with apoptotic nature in interferon (IFN)-and all-trans-retinoic acid (RA)-induced tumor cells. To reveal its biological rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
168
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(178 citation statements)
references
References 36 publications
10
168
0
Order By: Relevance
“…Consistent with this finding, we further demonstrated that GRIM-19 is localized in the mitochondria, associates with mitochondrial complex I, and plays essential roles in the assembly and enzymatic activity of complex I. 14 Based on its primary function in mitochondria, GRIM-19 has been recently suggested to be re-named as NADH dehydrogenase (ubiquinone) 1 alpha subcomplex 13 (NDUFA13) by HUGO Gene Nomenclature Committee (HGNC).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Consistent with this finding, we further demonstrated that GRIM-19 is localized in the mitochondria, associates with mitochondrial complex I, and plays essential roles in the assembly and enzymatic activity of complex I. 14 Based on its primary function in mitochondria, GRIM-19 has been recently suggested to be re-named as NADH dehydrogenase (ubiquinone) 1 alpha subcomplex 13 (NDUFA13) by HUGO Gene Nomenclature Committee (HGNC).…”
supporting
confidence: 78%
“…GRIM-19 was originally claimed as a nuclear protein, 10 but was later shown to be a mitochondrial protein. 11,12,14 In a recent review by Kalvakolanu, 34 it was proposed that GRIM-19 may initiate apoptosis, like cytochrome c and AIF, by translocation from the mitochondria to the nucleus upon IFN-b/RA stimulation. To test this hypothesis, we analyzed the cellular localization of GRIM-19, as well as other MRC subunit proteins, in the absence and presence of IFN-b/RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First-strand cDNA was synthesized from 3-5 mg of total RNA by oligo(dT) 15 primed reverse transcription with Expand Reverse Transcriptase (Roche Applied Science, Mannheim, Germany). The synthesized cDNA was subjected to PCR by using a pair of primers: 5¢-ATGCAAGAACCAAGGCGAGT-3¢ and 5¢-CAGAGCATTTCCGTCCCA-3¢ to amplify the GRIM-19-encoding fragment.…”
Section: Detection Of Mutation In Grim-19 Genementioning
confidence: 99%
“…13 Subsequently, GRIM-19 was demonstrated to be a new subunit of the mitochondrial NAPDH:ubiquinone oxidoredutase (respiratory chain complex I) and is essential for the complex I assembly, activity and maintenance of mitochondrial membrane potential. [14][15][16][17] Disruption of mitochondrial transmembrane potential by GRIM-19 mutants enhances the cells' sensitivity to apoptotic stimuli. 17 Furthermore, GRIM-19 has also been shown to repress the activity of the Signal Transducer and Activator of Transcription 3 (Stat3) and inhibit v-Src-induced oncogenic transformation and metastatic behavior of cells.…”
Section: Introductionmentioning
confidence: 99%